Evidence of Language Development Using Brief Animated Stimuli: A Systematic Review - Vlachou, Triantafyllia I; Kambanaros, Maria; Plotas, Panagiotis; Georgopoulos, Voula Chris (My University, 2024)
There is limited evidence regarding the effect of animation compared to static pictures on children's language development. The aim was to systematically review the available literature for evidence concerning the effect of brief animation on spoken language responses (receptive-listening or expressive-speaking) in typically developing (TD) children aged 3 to 9 years. Five databases were searched, resulting in seven included studies. The characteristics of animated stimuli, the manner of presentation, and the language-related tasks were recorded, and questions were posed about the effect of brief animation on children's receptive and expressive language abilities. The evidence suggests that animation may have a positive effect on expressive language abilities of children compared to static pictures. As far as the effect of animation on receptive language performance is concerned, the evidence is less concrete. Future directions regarding the potential of animation on language development are discussed.
Keywords: animation; language development; speech language pathology; typically developing children